2014
DOI: 10.1016/j.virusres.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin- and serine proteases-dependent uptake of porcine epidemic diarrhea virus into Vero cells

Abstract: Porcine epidemic diarrhea virus (PEDV), a member of the genus Alphacoronavirus, is a causative agent of porcine enteric disease characterized by acute watery diarrhea and dehydration in sucking piglet. Similar to other coronaviruses, PEDV spike protein mediates its cell entry by binding to cellular receptors and inducing membrane fusion between viral envelopes and cellular membranes. However, the entry mechanism of PEDV is not studied. Here, we determined the entry mechanism of PEDV into Vero cells. Our data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 36 publications
5
34
1
Order By: Relevance
“…Our previous published research found that TGEV can be internalized into IPEC-J2 cells, however the mechanism of TGEV entry is still not known. It has been confirmed that PEDV invades via clathrin-mediated endocytosis independent of caveolin-mediated endocytosis (Park et al, 2014). Our results suggest that TGEV infection reduces in clathrin or caveolin targeting shRNAs cells.…”
Section: Discussionsupporting
confidence: 77%
“…Our previous published research found that TGEV can be internalized into IPEC-J2 cells, however the mechanism of TGEV entry is still not known. It has been confirmed that PEDV invades via clathrin-mediated endocytosis independent of caveolin-mediated endocytosis (Park et al, 2014). Our results suggest that TGEV infection reduces in clathrin or caveolin targeting shRNAs cells.…”
Section: Discussionsupporting
confidence: 77%
“…5). It was previously reported that PEDV enters Vero cells through an initial endocytic uptake, followed by the viral fusion between the PEDV S and host endosomal membrane (Park et al, 2014;Liu et al, 2016). This is consistent with the results that the cellassociated PEDV was significantly higher at 37°C than 4°C regardless of the presence of PC10, PEDV-negative IgG, or DMEM alone, indicating that PEDV is taken up by cells through endocytosis more efficiently at 37°C than at 4°C.…”
Section: Discussionsupporting
confidence: 92%
“…Many viruses, including PEDV, utilize receptor-mediated endocytosis to gain entry into the host cells (Park et al, 2014). During the endocytic entry processes, viruses or viral genome translocate to cytoplasm (endosomal escapes) and initiate virus replication.…”
Section: Discussionmentioning
confidence: 99%